Fusobacterium necrophorum in ruminal contents and on the ruminal wall of cattle - K.R. Bedwell; N. Wallace; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1998)
Fusobacterium necrophorum was quantified from ruminal contents and ruminal wall tissue collected at slaughter. Livers were examined and scored for abscesses. The mean concentration of F. necrophorum on the ruminal wall ranged from 2.9 x 103 to 6.1x 105 per cm2 . The dorsal sac had the lowest counts, and dorsal blind and ventral sacs had the highest counts of F. necrophorum adherent to the ruminal wall. The concentrations of F. necrophorum in ruminal contents and on the ruminal wall did not appear to be related to presence or absence of abscessed livers or to severity of abscesses.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Fusobacterium necrophorum; Ruminal contents; Ruminal wall